High-Frequency Variability of Bacterioplankton in Response to Environmental Drivers in Red Sea Coastal Waters - Ansari, Mohd Ikram; Calleja, Maria LI.; Silva, Luis; Viegas, Miguel; Ngugi, David Kamanda; Huete-Stauffer, Tamara Megan; Morán, Xosé Anxelu G. (Frontiers in Microbiology, 2022)
Autotrophic and heterotrophic bacterioplankton are essential in the biogeochemistry of tropical ecosystems. However, the processes that govern their dynamics are not well known. We provide here a high-frequency assessment of bacterial community dynamics and concurrent environmental factors in Red Sea coastal waters. Weekly sampling of surface samples during a full annual cycle at an enclosed station revealed high variability of ecological conditions, which was mirrored by changes in major bacterioplankton communities. The temperature ranged from 23 to 34°C during the sampled period. Autotrophic (Synechococcus, 1.7 – 16.2 x 104 cells mL-1) and heterotrophic bacteria (1.6 – 4.3 x 105 cells mL-1) showed two maxima in abundance in spring and summer while minima were found in winter and autumn. High nucleic acid content (HNA) heterotrophic cells peaked in July, but their contribution to the total cell counts (35–60%) did not show any clear seasonal pattern. Actively respiring cells (CTC+) contributed between 4 and 51% to total heterotrophic bacteria, while live cells (membrane-intact) were consistently over 90%. 16S rRNA amplicon sequencing revealed a predominance of Proteobacteria in summer and autumn (>40%) and a diminished contribution in winter (21–24%), with members of the Alphaproteobacteria class dominating throughout the year. The contribution of the family Flavobacteriaceae was maximum in winter (21%), coincident with the lowest level of Rhodobacteraceae (6%). Temperature and chlorophyll-a and dissolved organic carbon concentrations were the environmental variables with the largest effects on bacterial abundances and diversity patterns.